Adsorption mechanism and effectiveness of phenol and tannic acid removal by biochar produced from oil palm frond using steam pyrolysis - Lawal, Abubakar Abdullahi; Hassan, Mohd Ali; Ahmad Farid, Mohammed Abdillah; Tengku Yasim-Anuar, Tengku Arisyah; Samsudin, Mohd Hafif; Mohd Yusoff, Mohd Zulkhairi; Zakaria @ Mamat, Mohd Rafein; Mokhtar, Mohd Noriznan; Shirai, Yoshihito (Elsevier, 2021)
In order to meet the growing demand for adsorbents to treat wastewater effectively, there has been increased interest in using sustainable biomass feedstocks. In this present study, the dermal tissue of oil palm frond was pyrolyzed with superheated steam at 500 °C to produce nanoporous biochar as bioadsorbent. The effect of operating conditions was investigated to understand the adsorption mechanism and to enhance the adsorption of phenol and tannic acid. The biochar had a microporous structure with a Brunauer-Emmett-Teller surface area of 422 m2/g containing low polar groups. The adsorption capacity of 62.89 mg/g for phenol and 67.41 mg/g for tannic acid were obtained using 3 g/L biochar dosage after 8 h of treatment at solution pH of 6.5 and temperature of 45 °C. The Freundlich model had the best fit to the isotherm data of phenol (R2 of 0.9863), while the Langmuir model best elucidated the isotherm data of tannic acid (R2 of 0.9632). These indicated that the biochar-phenol interface was associated with a heterogeneous multilayer sorption mechanism, while the biochar-tannic acid interface had a nonspecific monolayer sorption mechanism. The residual concentration of 26.3 mg/L phenol and 23.1 mg/L tannic acid was achieved when treated from 260 mg/L three times consecutively with 1 g/L biochar dosage, compared to a reduction to 72.3 mg/L phenol and 69.9 mg/L tannic acid using 3 g/L biochar dosage in a single treatment. The biochar exhibited effective adsorption of phenol and tannic acid, making it possible to treat effluents that contain varieties of phenolic compounds.